2020
DOI: 10.3390/jmse9010003
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Benefit Evaluation on Promising Strategies in Compliance with Low Sulfur Policy of IMO

Abstract: According to the amendment of the “International Convention for the Marine Prevention of Pollution from Ships” (MARPOL), Annex VI stating that the sulfur content in marine fuel oil cannot exceed 0.5 wt. % came into effect in 2020. This study uses cost-benefit analysis method to evaluate the feasibility and implementation benefits of those strategies. A container ship serving on the ship route is selected as a representative. It is found that the very low-sulfur fuel oil (VLSFO) strategy has a higher total incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The cost of retrofitting the scrubber will be 327 USD/kW [13]. The price for retrofitting the scrubber is lower for the larger engine.…”
Section: Installing Scrubber Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…The cost of retrofitting the scrubber will be 327 USD/kW [13]. The price for retrofitting the scrubber is lower for the larger engine.…”
Section: Installing Scrubber Technologymentioning
confidence: 99%
“…By installing a scrubber, the number of TEUs on board the ship will also decrease due to scrubber's component which may be installed on the ship. It will decrease about 1% of the total TEU on board the ship [13]. For the case study, the price of the IFO/HFO is around 478.5 USD/MT [10].…”
Section: Installing Scrubber Technologymentioning
confidence: 99%
“…Wu and Lin [9] evaluated the cost-benefit analysis method in terms of the feasibility and implementation benefits of these strategies, that is, the use of very low-sulfur fuel oil and scrubber for stricter environmental regulations. A container ship serving the shipping route was selected as a representative example.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study result claims that international laws related to emissions do not affect the economy at the port. The use of low sulphur fuel in compliance with the IMO policy also was proven as an appropriate option for long term use, according to a costbenefit analysis conducted by Wu and Lin [13]. However, this study has not yet considered parameters such as shipping routes, ship types and age.…”
Section: Introductionmentioning
confidence: 99%
“…Rahm [11] concluded that promoting the lowsulphur regulation will be a company competitive advantage. At the same time, Wu and Lin found [13] that low sulphur usage will benefit the company in the long term with cost consideration. Sys et al [12] also ensured that the port economy would not suffer because of this new, more expensive, low sulphur fuel.…”
Section: Introductionmentioning
confidence: 99%